Induksi Organogenesis pada Mikropropagasi Anggrek Vanda tricolor Lindl. serta Deteksi Variasi Genetik Hasil Perbanyakan dengan RAPD - RINDANG DWIYANI (Agrotrop : Journal on Agriculture Science, 2016)
Induction of Organogenesis on Micropropagation of Vanda tricolor Orchidand Detection of Genetic Variation of the Progenies Using RAPD Marker.Research concerning on micropropagation of Vanda tricolor orchid and detection of geneticvariation among the progenies has been conducted in the year of 2015. The objective of theresearch was to obtain the most appropriate explant type for inducing organogenesis and toobserve genetic variation of the progenies using Random Amplification of Polymorphic DNA(RAPD). Various pieces of organ from 18 month old-seedlings were used as material ofmicropropagation, i.e. shoot tip, shoot base, leaf tip and leaf base. Explants were planted onMS medium without plant growth regulator. The percentage of explant producing shoots andthe average number of shoots per-explant were observed at 12 weeks after planting. Progeniesresulted from the micropropagation were then analysed using RAPD with 5 primers, i.e.OPA8 (5’ GTGACGTAGG 3’), OPA9 (5’ GGGTAACGCC 3’), OPA10 (5’ GTGATCGCAG3’), OPA11 (5’ CAATCGCCGT 3’), OPA13 (5’ CAGCACCCAC 3’). The results showedthat the most appropriate explant for inducing organogenesis was shoot base. Analysis ofRAPD showed that the slight variation was detected between mother plant and the progeniesand also among the progenies. The results obtained from the current research are promisingand suggests that RAPD markers can be utilized as a simple molecular tool to assess thegenetic variation of plants derived in-vitro.